2018
DOI: 10.1002/aenm.201801191
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency (LixCu1−x)2ZnSn(S,Se)4 Kesterite Solar Cells with Lithium Alloying

Abstract: The performance‐boosting effect of alkali treatments is well known for chalcogenide thin‐film solar cells based on Cu(In,Ga)Se2 (CIGS) and Cu2ZnSn(S,Se)4 (CZTSSe–kesterite) absorbers. In contrast to heavier alkali elements, lithium is expected to alloy with the kesterite phase leading to the solid solution (LixCu1−x)2ZnSn(S,Se)4 (LCZTSSe), which offers a way of tuning the semiconductor bandgap by changing the ratio Li/(Li+Cu). Here is presented an experimental series of solution‐processed LCZTSSe with lithium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 45 publications
4
98
0
7
Order By: Relevance
“…Also, the PLQY value of 1 Â 10 À2 % is consistent with recent reports of 1.5 Â 10 À3 % measured on a CZTSe single crystal 57 and of 3 Â 10 À3 % on 11.6% efficient Li-doped CZTSSe solar cells. 69 In these solar cells the lifetime did not change significantly with Li-doping, while the PLQY and net doping density increased, again inline with our predictions. With regards to the calculated minority carrier lifetimes, we point out that the small estimated lifetimes for CZTS and CZTSe are in good agreement with recent findings indicating that reported carrier lifetimes for kesterites are often overestimated and that (typical) real lifetimes are in fact below 1 ns.…”
Section: View Article Onlinesupporting
confidence: 88%
“…Also, the PLQY value of 1 Â 10 À2 % is consistent with recent reports of 1.5 Â 10 À3 % measured on a CZTSe single crystal 57 and of 3 Â 10 À3 % on 11.6% efficient Li-doped CZTSSe solar cells. 69 In these solar cells the lifetime did not change significantly with Li-doping, while the PLQY and net doping density increased, again inline with our predictions. With regards to the calculated minority carrier lifetimes, we point out that the small estimated lifetimes for CZTS and CZTSe are in good agreement with recent findings indicating that reported carrier lifetimes for kesterites are often overestimated and that (typical) real lifetimes are in fact below 1 ns.…”
Section: View Article Onlinesupporting
confidence: 88%
“…The Li alloying and band gap tuning are also achieved by Lafond et al [25] from a ceramic synthesis route. Cabas-Vidani et al [27] confirmed the lithium alloying in the kesterite thin films (Li x Cu 1−x ) 2 ZnSn(S,Se) 4 in the range x=0 to 0.12 as measured by inductively coupled plasma mass spectrometry (ICP-MS), and a widening of the bandgap from 1.05 to 1.18 eV was observed. Morphology improvement and apparent carrier concentration increase from 3×10 15 cm −3 to 5×10 16 cm −3 was observed when increasing x from 0 up to 0.07, and a corresponding device had an active area efficiency of 12.2%.…”
Section: Lithium (Li)mentioning
confidence: 89%
“…Although the results and the explanation on the effect of Li doping/alloying differ and even contrast to each other, partially due to variation in material preparation conditions and matrix composition, some conclusions can be drawn based on the available reports [23][24][25][26][27][28][29][30][31][32]: (1) Li alloys with CZTS and widens the band gap of (Li x Cu 1−x ) 2 ZnSn(S,Se) 4 [24,25,27]; (2) incorporation of Li to kesterite is sensitive to Na so that Li alloying is more easily achieved without Na, in the ceramic route [25] or on quartz substrate, or using a blocking layer to prevent Na diffusion from SLG [24,27]. The presence of Na diffused from SLG greatly reduces the Li doping concentration [23,26]; (3) Li doping/alloying improves photovoltaic performance regardless the doping concentration, however, the mechanism on how Li doping/alloying improves device performance remains unclear.…”
Section: Lithium (Li)mentioning
confidence: 98%
“…However, in 2017, Huang et al reported that the electrical resistivity and optical band gap of CuInSe 2 were considerably enhanced by substitution of Li for Cu . Most recently, Cabas‐Vidani et al reported the high‐efficiency (Li x Cu 1 –x ) 2 ZnSn(S,Se) 4 kesterite solar cells with lithium alloying . Their champion device exhibits an efficiency of 11.6% (12.2% active area) for x = 0.06, close to the world record value of 12.6%.…”
Section: Introductionmentioning
confidence: 71%